Gaya Hidup Tokoh Haia dalam Novel Laut Tengah: Perspektif Bourdieu - Sofiana, Ayu; Apriyani, Tristanti (Lingua Susastra, 2025)
This study examines the representation of the female protagonist’s lifestyle in Berliana Kimberly’s novel Laut Tengah through Pierre Bourdieu’s theory of practice, especially habitus, capital, and field. The novel portrays Haia, a high‑achieving Muslim student who negotiates modernity, religiosity, and family pressure, yet her lifestyle practices have rarely been analyzed from a Bourdieusian sociological perspective. Using a qualitative descriptive method, this research takes Laut Tengah (2024) as the material object and focuses on the construction of Haia’s lifestyle as reflected in narrative descriptions, dialogues, and everyday scenes. Data were collected through close reading and note‑taking, then analyzed using an interactive model involving data reduction, matrix‑based data display, and conclusion drawing. The findings reveal three interrelated lifestyle configurations—independent, simple, and modern—emerging from the interaction between limited economic capital, high cultural capital as an outstanding student, and symbolic capital derived from a religio‑modern image. These configurations function as symbolic strategies for negotiating family‑based symbolic violence, gaining legitimacy in academic and urban spaces, and articulating a modern Muslim female identity within the demands of class and popular culture.